2018
DOI: 10.1039/c8nr03571g
|View full text |Cite
|
Sign up to set email alerts
|

Long-lived luminescence of colloidal silicon quantum dots for time-gated fluorescence imaging in the second near infrared window in biological tissue

Abstract: Boron (B) and phosphorus (P) codoped silicon quantum dots (Si QDs) are dispersible in polar solvents without organic ligands and exhibit photoluminescence (PL) in the first (NIR-I) and second (NIR-II) near infrared (NIR) windows in biological tissues due to the optical transition from the donor to acceptor states. We studied the relationship between the PL wavelength, lifetime and quantum yield (QY) of the colloidal solution and the composition of the starting material for the preparation. We found that the PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…6, which has been reported very recently. 20,44,45,52 Di®erent from other optical-chopper-based TG methods (OC-(i), OC-(ii), and OC-(iii)) that use delay units and TTL signals for synchronization, OC-(iv) employs a single optical chopper and spatial alignment of the excitation/emission beam spots with the chopper, which leads to a¯xed phase di®erence between the excitation and detection (blue and red pulse trains, respectively, in Fig. 6(a)) for synchronization in TG detection.…”
Section: Tg Implementation Based On Optical Choppersmentioning
confidence: 99%
See 1 more Smart Citation
“…6, which has been reported very recently. 20,44,45,52 Di®erent from other optical-chopper-based TG methods (OC-(i), OC-(ii), and OC-(iii)) that use delay units and TTL signals for synchronization, OC-(iv) employs a single optical chopper and spatial alignment of the excitation/emission beam spots with the chopper, which leads to a¯xed phase di®erence between the excitation and detection (blue and red pulse trains, respectively, in Fig. 6(a)) for synchronization in TG detection.…”
Section: Tg Implementation Based On Optical Choppersmentioning
confidence: 99%
“…Sakiyama et al demonstrated TG imaging in the NIR-II range based on OC-(iv). 44 Further, Zhu et al utilized the OC-(iv) approach for TG detection and demonstrated the applications including TG luminescence spectra measurement and fast luminescence lifetime imaging. 45,52 Our group also built a system based on OC-(iv).…”
Section: Tg Implementation Based On Optical Choppersmentioning
confidence: 99%
“…However, there is no need to detect the microsecond-delay luminescence with nanosecond shutters, and a wide range of technologies were developed in the past decades to reduce the cost for time-resolved detection of phosphorescence and delayed fluorescence (Marriott et al, 1991(Marriott et al, , 1994Verwoerd et al, 1994; FIGURE 1 | Schematic of pinhole shifting for scanning imaging of the delayed luminescence. Vereb et al, 1998;Connally, 2011;Jin, 2011;Jin and Piper, 2011;Jin et al, 2014;Zhang et al, 2014;Zheng et al, 2016;Sakiyama et al, 2018;Zhu andShu, 2018, 2019;Zhu et al, 2018b;Yang et al, 2019;Deng et al, 2020). Some methods based on CW excitation were even developed to achieve time-resolved luminescence detection (Nuñez et al, 2013;Petrášek et al, 2016;Zhu, 2019).…”
Section: Overview Of Time-resolved Techniquesmentioning
confidence: 99%
“…Most of these techniques are mainly used in detecting nanosecond-delayed fluorescence. As the developments of phosphorescence, delayed fluorescence and upconversion luminescence materials, these materials could emit luminescence with a delay time over microseconds or milliseconds (Marriott et al, 1991(Marriott et al, , 1994Verwoerd et al, 1994;Vereb et al, 1998;Connally et al, 2006;Connally and Piper, 2008;Bünzli, 2010;Gahlaut and Miller, 2010;Connally, 2011;Jin, 2011;Jin and Piper, 2011;Damayanti et al, 2013;Yang et al, 2013Yang et al, , 2019Grichine et al, 2014;Hirvonen et al, 2014;Jin et al, 2014;Lu et al, 2014;Zhang et al, 2014Zhang et al, , 2018Bergmann et al, 2016;Pominova et al, 2016;Zheng et al, 2016;Zhu et al, 2016Zhu et al, , 2018aBui et al, 2017;Chen T. et al, 2017;Wang et al, 2017;Sakiyama et al, 2018;Zhu andShu, 2018, 2019;Deng et al, 2020;Liu et al, 2020), greatly reducing the requirement of temporal resolution and the cost of the instruments. Combining with the use of low-cost shutters and automatic synchronization methods, CW light sources and common cameras were successfully used to accomplish the time-resolved luminescence detection with the temporal resolution ranging from microseconds to milliseconds (Marriott et al, 1991(Marriott et al, , 1994Verwoerd et al, 1994;…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation